Assessing Spanish-speaking immigrant parents' perceptions of climate at a New Language Immersion School: A critical analysis using "Thinking with Theory" - David Aguayo; Lisa M. Dorner (Arizona State University, 2017)
Parent involvement in schools is often developed through one-way, deficit-oriented relationships, where information flows from schools to families and parents are perceived to lack some capacity or knowledge. However, little is known about the conditions facing Spanish-speaking families at Spanish language immersion schools, which presumably might employ fewer deficit perspectives due to the language and culture focus of their educational model. In turn, this study asked: How does school climate discourse shape Spanish-speaking parents' abilities to engage at a Spanish immersion elementary school (SIES)? Do parents enact relational power at SIES, and if so, how? Data analysis centered on school climate surveys completed by 19 Spanish-speaking mothers. Framed by Ecologies of Parental Engagement (EPE) and Foucault's concepts of power, the study ultimately examined not only parent perceptions, but also the research project and its own deficit-driven norms. Findings include: While parents reported trusting the school and teachers, many felt discouraged in SIES's climate. Some blamed their level of involvement on their own (lack of) language or ability. Analyses also explore how the language immersion school and design of the research project-despite good intentions-were not bridging the gap between hegemonic English-speaking society and Spanish-speaking families. The discussion then considers the implications for school climate, parent engagement policies, and research at diverse multilingual schools.